2010
DOI: 10.1155/2010/904767
|View full text |Cite
|
Sign up to set email alerts
|

Detection of EBV, HBV, HCV, HIV-1, HTLV-I and -II, and SMRV in Human and Other Primate Cell Lines

Abstract: The high prevalence of contaminated cell cultures suggests that viral contaminations might be distributed among cultures. We investigated more than 460 primate cell lines for Epstein-Barr (EBV), hepatitis B (HBV), hepatitis C (HCV), human immunodeficiency virus type 1 (HIV-1), human T-cell leukemia/lymphoma virus I and II (HTLV-I/-II), and squirrel monkey retrovirus (SMRV) infections for risk assessment. None of the cell lines were infected with HCV, HIV-1, or HTLV-I/-II. However, one cell line displayed rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 45 publications
(46 reference statements)
1
33
0
1
Order By: Relevance
“…The DOHH-2 cell line was originally categorized as EBV negative (16) and a cell line vendor, Deutsche Sammlung von Mikroorganismen und Zellkulturen (DSMZ), classifies it as EBV negative. Nevertheless, a previous study showed the presence of EBV in DOHH-2 cells by PCR analysis with EBV episomes detected in only a small fraction of cells by FISH (17). Since the DOHH-2 cell line was derived by the clonal expansion of a mixed EBV negative and EBV positive culture as described by DSMZ, it is possible that there was carryover of a small percentage of EBV positive cells during the selection of EBV negative cells.…”
Section: Resultsmentioning
confidence: 99%
“…The DOHH-2 cell line was originally categorized as EBV negative (16) and a cell line vendor, Deutsche Sammlung von Mikroorganismen und Zellkulturen (DSMZ), classifies it as EBV negative. Nevertheless, a previous study showed the presence of EBV in DOHH-2 cells by PCR analysis with EBV episomes detected in only a small fraction of cells by FISH (17). Since the DOHH-2 cell line was derived by the clonal expansion of a mixed EBV negative and EBV positive culture as described by DSMZ, it is possible that there was carryover of a small percentage of EBV positive cells during the selection of EBV negative cells.…”
Section: Resultsmentioning
confidence: 99%
“…Detection of EBV, HBV, HCV, HIV-1, HIV-2, HTLV-I/II, MLV, and SMRV was carried out as described previously (Uphoff et al 2010(Uphoff et al , 2015.…”
Section: Analyses Of Mycoplasma and Viral Contaminationsmentioning
confidence: 99%
“…NK-92 is an established and well-characterized homogeneous cell line that has been successfully reproduced and expanded using good manufacturing practice (GMP)-compliant cryopreserved master cell banks. 110 It is a continuously expanding line and "limitless" in number, allowing the 119 While most groups agree that 1,000 cGy of radiation is sufficient to prevent engraftment of NK-92 cells with minimal effect on their in vitro cytotoxicity, irradiation prior to infusion is likely to negatively impact their in vivo proliferation, persistence, and long-term antitumor efficacy. 100 The efficacy of CAR-T cells is accepted to be dependent on persistence, 4,67 and similarly, the in vivo efficacy of adoptively infused NK cells has been shown to depend on their in vivo expansion and persistence.…”
Section: Studies With Car-modified Nk Cell Linesmentioning
confidence: 99%